Semantics Analysis of Sentences, Utterances, and Presuppositions in The Story Five Feet Apart by Rachael Lippincott - Emir Fahim Ramzy; Fajar Shakti Wiraatmaja; Keyza Alifah Mokginta; Rahmawati Jaymitha; Hilma Safitri (INDO PUBLISHING, 2025)
Rachael Lippincott's 2019 short tale